Майстер пензля і слова (документи ЦДАМЛМ України до біографії художника-графіка Валентина Литвиненка) - Аксьом, А. (Архіви України, 2008)
The publication describes the documents respecting life and creative develop ment of V. Lytvynenko, a Ukrainian graphic artist (1908–1979). His personal fond, preserved at TsDALM of Ukraine, includes newspaper drawings, books and maga zines illustrations, posters, postcards, lyric landscapes, as well as some materials related to his creative work.